2022
DOI: 10.3389/fphar.2022.934057
|View full text |Cite
|
Sign up to set email alerts
|

Epimedium koreanum Nakai–Induced Liver Injury—A Mechanistic Study Using Untargeted Metabolomics

Abstract: Epimedii Folium is widely used worldwide as an herbal supplement, and the risk of its induced liver damage has emerged in recent years. Our preliminary study has found that, among several Epimedii Folium species specified in the Chinese Pharmacopoeia, Epimedium koreanum Nakai has a more severe propensity for hepatotoxicity. However, the mechanism of hepatotoxicity of Epimedium koreanum Nakai is still unclear. In this study, untargeted metabolomics was performed to analyze the serum and liver tissue to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…NAC are generally less toxic, but this does not guarantee they are all safe. Recent studies have confirmed that triptolide [ 242 ], toosendanin [ 243 ], aurantio-obtusin [ 244 ], and Epimedium koreanum Nakai [ 245 ] all induced hepatotoxicity by triggering ferroptosis. NAC that triggers ferroptosis in HSCs and HCC cells may also cause damage to healthy hepatocytes.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…NAC are generally less toxic, but this does not guarantee they are all safe. Recent studies have confirmed that triptolide [ 242 ], toosendanin [ 243 ], aurantio-obtusin [ 244 ], and Epimedium koreanum Nakai [ 245 ] all induced hepatotoxicity by triggering ferroptosis. NAC that triggers ferroptosis in HSCs and HCC cells may also cause damage to healthy hepatocytes.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…Epimedium koreanum Nakai, one of the species of Epimedii Folium, is widely used worldwide as an herbal supplement but has a severe propensity for hepatotoxicity. The in vivo study investigating the mechanism of its hepatotoxicity identified the ferroptosispromoting protein ACSL4 was significantly up-regulated, and GPX4 and System Xc − were significantly down-regulated, indicating the mechanism of hepatotoxicity of Epimedium koreanum Nakai may related to the induction of ferroptosis in hepatocytes [82].…”
Section: The Effects Of Natural Products On Enzymes Involving Lipid M...mentioning
confidence: 99%